2019
DOI: 10.3390/rs12010108
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Cyclone Intensity Estimation Using Multi-Dimensional Convolutional Neural Networks from Geostationary Satellite Data

Abstract: For a long time, researchers have tried to find a way to analyze tropical cyclone (TC) intensity in real-time. Since there is no standardized method for estimating TC intensity and the most widely used method is a manual algorithm using satellite-based cloud images, there is a bias that varies depending on the TC center and shape. In this study, we adopted convolutional neural networks (CNNs) which are part of a state-of-art approach that analyzes image patterns to estimate TC intensity by mimicking human clou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 58 publications
0
52
0
Order By: Relevance
“…Tropical cyclones are among the most devastating natural disasters owing to their great potential for loss of human life, significant economic decline and severe environmental damage [1][2][3]. The Southwestern Indian Ocean is one of the main tropical cyclone areas 2012 to 2019; (ii) to investigate how the distance to Idai's trajectory related to vegetation damage, and (iii) to determine the degree of damage caused by the cyclone on different LULC classes.…”
Section: Introductionmentioning
confidence: 99%
“…Tropical cyclones are among the most devastating natural disasters owing to their great potential for loss of human life, significant economic decline and severe environmental damage [1][2][3]. The Southwestern Indian Ocean is one of the main tropical cyclone areas 2012 to 2019; (ii) to investigate how the distance to Idai's trajectory related to vegetation damage, and (iii) to determine the degree of damage caused by the cyclone on different LULC classes.…”
Section: Introductionmentioning
confidence: 99%
“…In [63 ], a multi‐layer neural network is proposed and trained to forecast the track of cyclones based on satellite images. The deep convolutional neural network (CNN) is employed to estimate the intensity of tropical cyclones based on satellite images in [64, 65 ]. It should be noted that AI systems estimate the tracks and intensity of hurricanes through mimicking human cloud pattern recognition.…”
Section: Enhancing Resiliencementioning
confidence: 99%
“…They concluded that their best model was competitive with existing methods such as the advanced Dvorak technique (ADT 32 ) and Satellite Consensus (SATCON 33 ). Lee et al 27 used a two-dimensional CNN (2D-CNN) and a three-dimensional CNN (3D-CNN) to analyze the relationship between multispectral geostationary satellite images and TC intensity. Their optimal model exhibited better performance (35%) than the existing model using the CNN-based approach with a single channel image.…”
Section: Introductionmentioning
confidence: 99%